New insight into ischemic stroke: Circadian rhythm in post-stroke angiogenesis - Zhang, Yuxing; Liu, Lijuan; Zhao, Xin; Yan, Siyang; Zeng, Fukang; Zhou, Desheng (Frontiers in Pharmacology, 2022)
The circadian rhythm is an endogenous clock system that coordinates and optimizes various physiological and pathophysiological processes, which accord with the master and the peripheral clock. Increasing evidence indicates that endogenous circadian rhythm disruption is involved in the lesion volume and recovery of ischemic stroke. As a critical recovery mechanism in post-stroke, angiogenesis reestablishes the regional blood supply and enhances cognitive and behavioral abilities, which is mainly composed of the following processes: endothelial cell proliferation, migration, and pericyte recruitment. The available evidence revealed that the circadian governs many aspects of angiogenesis. This study reviews the mechanism by which circadian rhythms regulate the process of angiogenesis and its contribution to functional recovery in post-stroke at the aspects of the molecular level. A comprehensive understanding of the circadian clock regulating angiogenesis in post-stroke is expected to develop new strategies for the treatment of cerebral infarction.